Ligand-Dependent Recruitment of the ErbB4 Signaling Complex into Neuronal Lipid Rafts - Li Ma; Yang Z. Huang; Graham M. Pitcher; Juli G. Valtschanoff; Howard S. Ying; Lin Feng; Bai Lu; Wen‐Cheng Xiong; Michael W. Salter; Richard J. Weinberg; Lin Mei (2003)
Neuregulin (NRG) regulates synapse formation and synaptic plasticity, but little is known about the regulation of NRG signaling at synapses. Here we show that the NRG receptor ErbB4 was localized in anatomically defined postsynaptic densities in the brain. In cultured cortical neurons, ErbB4 was recruited to the neuronal lipid raft fraction after stimulation by NRG. Along with ErbB4, adaptor proteins Grb2 and Shc were translocated to lipid rafts by NRG stimulation. In transfected human embryonic kidney 293 cells, the partitioning of ErbB4 into a detergent-insoluble fraction that includes lipid rafts was increased by PSD-95 (postsynaptic density-95), through interaction of the ErbB4 C terminus with the PDZ [PSD-95/Discs large/zona occludens-1] domains of PSD-95. Disruption of lipid rafts inhibited NRG-induced activation of Erk and prevented NRG-induced blockade of induction of long-term potentiation at hippocampal CA1 synapses. Thus, our results indicate that NRG stimulation causes translocation of ErbB4 into lipid rafts and that lipid rafts are necessary for signaling by ErbB4.